Distribution of earth leakage currents in railway systems with drain auto-transformers. - Chih-Ju Chou
This work presents a novel advanced methodology to accurately predict the earth leakage currents for analyzing the electrification railway systems with drain auto-transformers. The proposed methodology entails applying a decoupled technique to model the equivalent circuit while simultaneously considering the grounding network and the effects on mutual impedance between feeders. Also presented herein are several study cases, particularly with respect to how grounding resistance, span of auto-transformers, turn-ratio of auto-transformers, and location of ground faults influence the leakage currents. These study cases demonstrate that the computer program based on the proposed methodology can effectively analyze the leakage currents in the planning stage for developing railway systems
Keywords: Auto-transformer span; Computer program; Decoupled technique; Drain auto-transformers.; Earth leakage currents distribution; Earth leakage currents prediction; Electrification railway systems; Equivalent circuit modeling; Ground faults location; Grounding resistance; Mutual impedance; Railway systems; Turn-ratio.